2013
DOI: 10.1111/jpc.12129
|View full text |Cite
|
Sign up to set email alerts
|

Types and distribution of congenital heart defects associated with trisomy 21 in Singapore

Abstract: VSD was the most common congenital heart defect seen in trisomy 21 in our study. A high proportion (25.0%) of trisomy 21 patients with tetralogy of Fallot also had AVSDs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 15 publications
1
11
0
Order By: Relevance
“…Congenital heart defects have been reported at a rate of 40-60% (3,6). Association of CHD is one of the most important predictive factor affecting morbidity and mortality in these patients (5).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Congenital heart defects have been reported at a rate of 40-60% (3,6). Association of CHD is one of the most important predictive factor affecting morbidity and mortality in these patients (5).…”
Section: Discussionmentioning
confidence: 99%
“…AVSD has been reported as the most common congenital heart defect in children with DS (3). On the other hand, studies reported that prevalence and distribution of CHD among children with DS varies by regions and ethnic groups (3)(4)(5). The studies from western countries reported AVSD as the frequent defect in DS (3).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations